Optimisation of proteomic approaches to study the maternal interaction with gametes in sow's reproductive tract. Issue 3 (September 2015) - Aldarmahi, Ahmed; Al-Rabia, Mohammed
Abstract: The applications of 2DE and MS have been successfully used in many studies utilising different biological samples. The complex nature of cellular proteomes is a big challenge for proteomic technologies. Much effort has been applied to develop and improve the preparation techniques for proteomic samples to be able to detect the low abundant proteins. This is one of the major and unsolved challenges facing the proteomic analysis of biological samples. One partial remedy is to deplete the proteomic samples. In this study, we compared two techniques (acetone precipitation and commercial kit) for the cleaning and purification of oviductal and uterine horn secretory proteomes in primary cell culture system. The samples prepared from acetone precipitation and commercial kit 2-D clean up kit were compared by 2-dimentioanl electrophoresis. We found that no significant difference was observed in number of spots detected between the samples prepared by acetone precipitation technique to those prepared by commercial kit. Protein samples were run through strong cation exchange (SCX) liquid chromatography in order to fractionate samples of major proteins. Protein identification by mass spectrometry revealed a significant detection of low abundant proteins in comparing to high abundant proteins. In conclusion, acetone precipitation was found to be more efficient and cost effect technique. Depletion of proteomic samples from the most abundant protein species is strongly recommended to allow the mid and low abundant protein to be detected. A better resolution of the gels will be achieved by removing the major proteins such as albumin and immunoglobulin.